Education for Prevention of Cardiovascular Diseases in a Higher Education Institution Workers: ¡Avoiding absence from work! - Rojas Padilla, Isabel Cristina; Vergara López, Yury (MEDICA REVIEW. International Medical Humanities Review / Revista Internacional de Humanidades Médicas, 2020)
Cardiovascular diseases (CVD) are the cause of many deaths worldwide and the most paradoxical issue is that most of them can be prevented by acting on behavioural risk factors such as sedentary lifestyle, excess weight, inadequate diets, cigarette consumption and alcoholic beverages. Cardiovascular risk must be detected early to intervene it first and prevent it becomes a diagnosed disease. Promotion and prevention of healthy lifestyle habits prevent suffering and improve the quality of people’s life, even more in active working individuals who must interact in a social environment daily.